Associations between social inequality and tooth loss in a household sample of elderly Thai people aged ≥60 years old - Srisilapanan P. (2017)
© 2014 John Wiley & Sons AS and The Gerodontology Association. Published by John Wiley & Sons Ltd. Objective To assess the relationship between social inequality and the number of remaining teeth in an elderly Thai population. Background Having twenty or more remaining teeth is an important indicator of optimal oral health in the elderly. Methods The data for this study were derived from the Survey of Older Persons in Thailand, conducted by the National Statistical Office, based on face-to-face interviews with people aged ≥60. The total sample was 30 427. The oral health measure was self-reported remaining number of teeth. Income, education and possession of durable goods were utilised as measures of social inequality. Results More than half of the sample (57.0%) was women. The majority (73.2%) was in the age range 60-74 years old. Less than a fifth (15.5%) had 7 or more years of education. A third earned < 20 000 Thai Baht (THB) per annum (defined as poor). More than half (52.8%) of the sample had < 20 remaining teeth. There was a link between social inequalities and tooth loss. In the adjusted model, elderly people, who were older than 75, who were not under a married status, had a lower level of education, had a lower income, and who did not own luxury goods, were 2.84 (CI 95% 2.66-3.03), 1.31 (CI 95% 1.21-1.41), 1.44 (CI 95% 1.34-1.56), 1.12 (CI 95% 1.13-1.29) and 1.21 (CI 95% 1.13-1.29) times more likely to have 19 or fewer teeth remaining, respectively. Conclusion Social inequality is related to the number of remaining teeth in elderly Thai people.